Perancangan Sistem Informasi Penjualan Box dan Tempat Seserahan di â€œFâ€ Production Sruweng Berbasis Web dengan Framework Codeigniter - Aldi, Aldi Zubaidi; Dika, Riswondo Mahardiko; Sari, Fitriani Dwi Ratna (Politeknik Piksi Ganesha Indonesia, 2021)
The F Production shop is enganged in handicrafts such as offerings and boxes, has quite a lot of customers so a website-based sales information system is needed to make it easier for customers to buy products at the F Production Store without having to visit the store directly. Thatâ€™s why Store F requires an online sales information system based on a website which will later be integrated to manage all problems that occur in store F. The resulting system will be developed using the SDLC method, PHP Programming language, and with a MySQL database.